Annual report of the Women's Health Care Committee, Japan Society of Obstetrics and Gynecology, 2016. Issue 11 (November 2016) - Takamatsu, Kiyoshi; Kitawaki, Jo
Abstract: In order to improve women's quality of life, over the year leading up to June 2016, the Women's Health Care Committee of the Japan Society of Obstetrics and Gynecology focused upon: (i) breast management; (ii) influence of a therapy for gynecologic disease on physical condition; (iii) nonsurgical management of pelvic organ prolapse; (iv) survey of infectious diseases in Obstetrics and Gynecology in Japan; (v) health care for female athletes; (vi) a training program for women's health‐care advisers; and (vii) revising the Japanese guideline on hormone‐replacement therapy. In order to publicize the activities of our committee widely, the detailed activities of the seven subcommittees are described in this report, which is based on the Japanese version of the annual report (Acta Obst Gynaec Jpn 2016; 68 (6): 1404–1416).